1991
DOI: 10.1111/j.1365-2842.1991.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphoric acid and tannic acid on dentine collagen

Abstract: We examined the effects of phosphoric acid, the most common enamel etchant in composite resin therapy, on dentine collagen. Dentine collagen pretreated with 7M phosphoric acid was shown to be more susceptible to trypsin digestion than untreated collagen. This susceptibility increased with increasing duration of exposure to the acid. The results indicate that phosphoric acid induces a conformational change in dentine collagen (denaturation or perturbation) similar to that observed with 0.39 M HCl, which has a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 8 publications
0
23
0
2
Order By: Relevance
“…5 TEM images showed a clear and definite banding on the observed fibrils, revealing that when shrinkage is avoided, the CF are able to maintain their morphologic characteristics upon etching with 35% H 3 PO 4 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…5 TEM images showed a clear and definite banding on the observed fibrils, revealing that when shrinkage is avoided, the CF are able to maintain their morphologic characteristics upon etching with 35% H 3 PO 4 .…”
Section: Discussionmentioning
confidence: 94%
“…In fact, it has been shown that the dentin surface represents a complex substrate that needs to be treated with specific surface-energy enhancers (or primers) in order to render it acceptable for bonding. 4 The structural alterations of CF in some areas of etched dentin may be caused by the aggressiveness of the etchant 5 since dentin collagen, after demineralization, is susceptible to proteolytic degradation. 6 In spite of assumptions in the literature that etching dentin for 15 s may cause collagen denaturation and compromise dentin bonding, it never has been substantiated nor has it been proven that such changes occur in CF ultrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Previous studies have revealed that CFs might be partially altered by the aggressiveness 17 and the osmolarity 18 of the acid solutions. Even though there are no studies that have related alterations of CFs with structural modification of the hybrid layer formation 19,20 after the application of an adhesive agent, we may speculate that a proteolytic degradation of exposed CFs may negatively influence the adhesive process and its longevity.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of tannic acid use in dentistry as a desensitizing agent, astringent, and surface treatment for smear layer removal have been previously described (Bitter, 1989;Prati et al, 1992;Sabbak and Hassanin, 1998;Natsir et al, 1999;Okamoto et al, 1991;Tomiyama et al, 2004), but no information exists regarding its effect on the mechanical properties of dentin and adhesive-dentin interfaces. The present study showed that tannic acid significantly affected dentin matrix properties and resin-dentin bond strength; therefore, the null hypotheses must be rejected.…”
Section: Discussionmentioning
confidence: 99%